Comparison of an Effervescent Nozzle and a Proposed Air‐Core‐Liquid‐Ring (ACLR) Nozzle for Atomization of Viscous Food Liquids at Low Air Consumption. Issue 1 (11th August 2015) - Stähle, Philipp; Gaukel, Volker; Schuchmann, Heike P.
Abstract: Recent results regarding the effervescent atomization of viscous food‐based liquids reveal that an unfavorable slug flow is formed inside the nozzle for low gas to liquid ratios (GLRs). As a result, a very unsteady spray drop size is formed, which leads the nozzle to be unsuitable for an implementation in spray drying. In this study, we propose a modified nozzle design named ACLR (Air‐Core‐Liquid‐Ring) to establish the favorable annular flow inside the exit orifice. High‐speed imaging proved that the desired flow pattern was present in the investigated GLR range of 0.015–0.414 and for liquid viscosities of 0.001–0.308 Pa·s. Comparison with a conventional effervescent nozzle showed similar values of the time averaged Sauter mean diameter of the spray drops. Considering the temporal unsteadiness of the spray drop size, a considerable reduction can be achieved for viscous liquids and low GLRs by the proposed ACLR nozzle. Practical Applications: For an economic spray drying process, the highest possible dry matter content prior to drying is aspired. However, as feed viscosity increases rapidly with an increase in dry matter content, atomization is considerably hindered. The effervescent nozzle, originally invented in the field of combustion science, is reported to atomize viscous liquids into small spray drops at low gas consumption. Recent results of our group reveal that an unsuitable slug flow is formed inside the nozzle when food‐based liquids with elevated viscosities are atomized at low gas to liquid ratios. Consequently, the effervescent nozzle is not suitable for an implementation in spray drying. In this study, we propose a modified nozzle design that overcomes the drawbacks of a conventional effervescent nozzle. The Air‐Core‐Liquid‐Ring nozzle offers the possibility to save large amounts of drying energy of existing spray dryers as higher concentrated feeds might be used.